ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS X DALAM MENYELESAIKAN SPLDV - Anggita Tri Indahsari; Aflich Yusnita Fitrianna (IKIP Siliwangi, 2019)
This research is useful to describe the low ability students in problem solving as well as errors of students in the matter of the story SPLDV and provide an alternative settlement. This research was carried out with the method of qualitative and descriptive indicators and analysis tailored to the problem solving based on the analysis of polya and using descriptive qualitative methods. The subject of this research totalled 33 learners class X SMK in Cimahi school year 2018/2019. The collection of data on research using the method of observation, test, and an interview. From the results of the tests and interviews it is known that the basic concept on reserved SPLDV students are still less so there is confusion in resolving the matter, because students can only understand the problem of 2.57%, drafting plans of 8.63%, making plans and corrects return of 15%, then the conclusion is that the problem-solving ability of the students of SMK owned is still low.